PENGARUH PERBANDINGAN LIMBAH PADAT (SLUDGE) PABRIK KELAPA SAWIT DENGAN TANAH PODSOLIK MERAH KUNING SEBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Rahmawan, Dwi; Saputra, Sukemi Indra; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to determine the effect comparison Red Yellow Podzolic soil and sludge as growing media and get the best comparison that can support the growth and development of cocoa seedlings. The research was carried out experiments with 5 treatments using completely randomized design (CRD), each treatment was repeated four times so that there are 20 experimental units and each unit consists of 6 seed experiment so that the total population are120 seedlings. Treatments are: yellow red podzolic land only, 3 parts yellow red podzolic land: 1 part sludge, 2 parts yellow red podzolic land: 1 part sludge, 1 part yellow red podzolic land: 1 part sludgeand 1 part yellow red podzolic land : 2 part sludge with a ratio of parts by weight. Parameters measured were higher seed, stem diameter, number of leaves, leaf area,roots and crown ratio and dry of weight. Data were analyzed statistically and followed by Duncan's test at 5% level. Comparison of yellow red podzolic land with sludge as a soil media showed significant effect on plant height, stem diameter, number of leaves, leaf area, canopy ratio of dry weight of roots and seeds. Treatment of 1 part ground yellow red podzolic land: 1 part sludge showed the best results for the growth and development of cocoa seedlings. Keywords :cocoa, yellow red podzolic land, sludge